ANALISIS PENGELOLAAN MODAL KERJA DALAM RANGKA MENINGKATKAN PROFITABILITAS PADA KOPERASI SAWIT USAHA MANUNGGAL DESA SERESAM KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU PERIODE 2014-2018 - Anggraini, Retno; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Working capital is the main factor driving the operational of a business both companies and cooperatives, where working capital serves to finance all the daily operational needs of cooperatives. Determination of effective working capital will produce optimal profits. While improper working capital management will have an impact on cooperative profitability.This study aims to determine the management of working capital in order to increase profitability in Koperasi Sawit Usaha Manunggal Desa Seresam Kecamatan Seberida Kabupaten Indragiri Hulu for the last five years. Types and sources of data used in this study are secondary data, namely data obtained from cooperatives including cooperative financial statement data and other data related to research material.Based on the results of the study showed that the calculation of the activity ratio showed the total assets turnover and accounts receivable turnover decreased and showed that the accounts receivable turnover was still very low, while the cash turnover, working capital turnover, and inventory turnover fluctuated. The calculation of the liquidity ratio shows the current ratio, and the quick ratio has decreased, while the cash ratio has fluctuated. Calculations on profitability ratios indicate fluctuations in the ratios used over the past five years.Keywords: Working Capital, Activities, Liquidity, Profitability